The Interplay of Glucagon-Like Peptide-1 Receptor Trafficking and Signalling in Pancreatic Beta Cells - Marzook, Amaara; Tomas, Alejandra; Jones, Ben (Frontiers in Endocrinology, 2021)
The glucagon-like peptide 1 receptor (GLP-1R) is a class B G protein-coupled receptor (GPCR) which mediates the effects of GLP-1, an incretin hormone secreted primarily from L-cells in the intestine and within the central nervous system. The GLP-1R, upon activation, exerts several metabolic effects including the release of insulin and suppression of appetite, and has, accordingly, become an important target for the treatment for type 2 diabetes (T2D). Recently, there has been heightened interest in how the activated GLP-1R is trafficked between different endomembrane compartments, controlling the spatial origin and duration of intracellular signals. The discovery of “biased” GLP-1R agonists that show altered trafficking profiles and selective engagement with different intracellular effectors has added to the tools available to study the mechanisms and physiological importance of these processes. In this review we survey early and recent work that has shed light on the interplay between GLP-1R signalling and trafficking, and how it might be therapeutically tractable for T2D and related diseases.